Identifying of talented students at elementary schools using volleyball`s talent identification - Kusnanik, N.; Januarumi, F.; Muhamad; Yulfadinata, A.; Ayubi, N.; Pujijuniarto; Lumba, J.; Fenanlampir, A. (Proceedings of the Unima International Conference on Social Sciences and Humanities (UNICSSH 2022), 2023)
Volleyball is an interesting sport that can be played by many people in the world. Recently, volleyball matches have become an interesting spectacle that can be seen directly or through television program or youtube channels. Therefore, it is necessary to search for talented volleyball players. The purpose of this study was to implemented the talent identification model to identify young talented students in volleyball. Subjects of this study were 300 elementary students who active in the physical education with minimum height 150 cm, aged between 11 to 13 years olds. All subjects were measured for body mass, height, sitting height, standing reach, spam arm, and leg length. Subjects were also tested for vertical jump with 1 leg, vertical jump with 2 legs, shuttle run, multistage fitness test, flexibility, throw and catch tennis ball. Volleyball talent identification equation model`s by Kusnanik 2014 was used to analyzed the data. Results of the study showed that there was 23 students who were identified as young students elementary school in volleyball (9 female students and 14 male students). It can be concluded that model of talent identification in volleyball can be used as an alternative method to identify young talented students in volleyball.